Socio-Pedagogical Aspects Of Legal Culture Development In STUDENTS - et. al., Shadiev Safar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article comprehensively analyzes the scientific analysis of the socio-pedagogical aspects of improving the legal culture of students. Methodological aspects of improving the legal culture of the population, especially young people, analysis of pedagogically effective methods, forms and factors, as well as effective mechanisms to ensure the effectiveness of modern technologies to improve the legal culture of students, the formation of their legal culture. awareness and thus effective legal awareness is important to study modern technologies.